Orbit Determination of China’s Space Station Using Real ISL Measurements of the Tianzhou-6 Spacecraft - Haijian Fang; Fan Wang; Xueming Yu; Baohua Wang; Jiasong Wang; Yufan He; Minzhang Han; Dan Wang; Jingqi Huang (International Journal of Aerospace Engineering)
Under most circumstances, the current studies related to precision orbit determination (POD) using intersatellite link (ISL) measurements are limited to ISL ranging components. In this article, we would like to discuss the idea of jointly using the GNSS observations and ISL ranging and orientation measurements of the Tianzhou-6 (TZ-6) spacecraft to generate the orbit solutions of China’s space station (CSS). Motivated by the requirement of mission implementation, the data processing procedure of the ISL orientation measurements is introduced based on the TZ-6 spacecraft attitude. The partial derivatives and the differential correction approach in a batch least squares estimator are elaborated on. This combined POD method concentrates on the connection between orbit determinations performed on the TZ-6 spacecraft using GNSS observations and on CSS using ISL ranging and orientation measurements, respectively. Realistic force, ISL measurements, and reference frame models are utilized to account for additional major error sources. Finally, the estimated solutions then are compared to the precision orbit ephemerides (POEs) of CSS. The statistical results demonstrate the effectiveness of the combined POD method.